Equivalent Models of Corrugated Panels - Saavedra-Flores, E (2012)
The design of corrugated panels has wide application in engineering. For example corrugated panels are often used in roof structures in civil engineering. More recently corrugated laminates have been suggested as a good solution for morphing aircraft skins due to their extremely anisotropic behaviour. The optimal design of these structures requires simple models of the panels or skins that may be incorporated into multi-disciplinary system models. Thus equivalent material models are required that retain the dependence on the geometric parameters of the corrugated skins or panels. An homogenisation-based analytical model, which could be used for any corrugation shape, is suggested in this paper. This method is based on a simplified geometry for a unit-cell and the stiffness properties of original sheet. This paper outlines such a modelling strategy, gives explicit expressions to calculate the equivalent material properties, and demonstrates the performance of the approach using two popular corrugation shapes. © 2012 Elsevier Ltd. All rights reserved.